Physiological and Molecular Responses of Underutilized Genotype AHK-200 of Vegetable Melon (Cucumis melo var. melo) Against Drought Stress: Gas Exchange, Antioxidant Activity, and Gene Expression - Sudhakar Pandey; Waquar Akhter Ansari; Ram Krishna; Akhilesh Yadav; Durgesh Kumar Jaiswal; Bijendra Singh (Metabolites, 2025)
Background/Objectives: Drought stress is a significant environmental challenge that affects plant growth and productivity. Methods: In this study, an underutilized and better drought stress tolerance genotype of Cucumis melo var. melo, i.e., AHK-200, was investigated for drought tolerance potential, with special emphasis on various morphological, physiological, biochemical, and molecular parameters. Results: Our findings show that AHK-200 demonstrates superior drought tolerance with an enhanced root length, better water retention capacity, and stable cell membrane integrity under water deficit conditions. Physiologically, AHK-200 exhibited minimal reduction in relative water content (RWC) and photosynthetic efficiency (PN), along with increased stomatal conductance (gs) and chlorophyll content and reduced photoinhibition under drought stress. Biochemically, AHK-200 showed higher antioxidant enzyme activity (APX, CAT, SOD, GR, POD) and osmolyte accumulation (proline), which are critical for mitigating oxidative stress. At the molecular level, drought-related genes such as DREB2C, DREB2D, and RD22 were upregulated, supporting AHK-200 resilience to drought stress. Additionally, AHK-200 displayed elevated mineral concentrations, including Na, K, Ca, and Fe, which are essential for cellular homeostasis and stress adaptation. Conclusions: Overall, our study provides a comprehensive understanding of the drought tolerance mechanisms in AHK-200, highlighting its potential for use in breeding drought-tolerant genotypes in cucurbits and related crops. This research could guide future efforts in gene manipulation and transgenic development aimed at enhancing drought resistance and yield potential in crop plants. Furthermore, DREB2C, DREB2D, and RD22 transcription factors regulate many pathways related to stress; the overexpression of these genes may open a new avenue in melon improvement against drought stress.